Efeitos do pré-condicionamento isquêmico local e remoto aplicado em diferentes níveis de oclusão vascular sobre a variabilidade de frequência cardíaca e capacidade funcional de idosos - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2025)
The aging process leads to a series of physiological changes that, progressively reducing functional capacity. To mitigate these functional losses, ischemic preconditioning (IPC) may represent a promising strategy. Thus, the present study aimed to examine the effects of different IPC protocols, performed at varying levels of vascular occlusion, on functional capacity, subjective perception of effort (SPE), pain perception, and heart rate variability (HRV) in older adults. The study included 20 elderly individuals (68.2 ± 5.7 years), who underwent a randomized crossover experimental protocol across five sessions: control, IPC applied to the upper limbs (remote – R) and lower limbs (local – L) at 50% (IPC R 50% and IPC L 50%) and 100% (IPC R 100% and IPC L 100%) of the vascular occlusion level (VOL). In each session, functional capacity was assessed using the 6-minute walk test (6MWT) after IPC, pain perception was evaluated using the visual analog scale (VAS) during IPC, effort perception was measured via the Borg scale during the 6MWT, and HRV indices were collected during IPC, the 6MWT, and 10 minutes post-exercise. A significant increase in walking distance during the 6MWT was observed in the IPC R 100% (443.7 ± 69.44 m), IPC L 50% (446.14 ± 67.91 m), and IPC L 100% (452.69 ± 67.51 m) conditions compared to the control session (421.01 ± 72.60 m; p = 0.01; p < 0.0001; p < 0.001, respectively). Greater pain perception was reported in all IPC R 100% cycles (3.85 ± 2.25 a.u.; 4.70 ± 2.27 a.u.; 4.25 ± 2.33 a.u.) compared to IPC R 50% cycles (1.20 ± 1.67 a.u.; 1.35 ± 1.59 a.u.; 1.10 ± 1.55 a.u.) (p = 0.001; p < 0.001; p < 0.001, respectively), as well as in IPC L 100% cycles (5.05 ± 2.13 a.u.; 4.11 ± 1.61 a.u.; 3.95 ± 1.87 a.u.) compared to IPC L 50% cycles (1.62 ± 1.98 a.u.; 1.4 ± 1.75 a.u.; 1.30 ± 1.71 a.u.) (p < 0.001; p < 0.001; p = 0.001, respectively). No significant differences were observed in SPE during the 6MWT, nor were significant interactions detected in HRV-related variables. Our findings suggest that, when applied locally (IPC L), lower VOL (50%) appears to be as effective as higher VOL (100%) in promoting acute functional improvements in older adults while exposing them to lower pain levels. Conversely, when applied remotely (IPC R), functional gains seem to occur only when higher VOL (100%) is used. Longitudinal studies and/or protocols incorporating more ischemia cycles per session appear necessary to induce significant modifications in SPE as well as HRV in older individuals.
Keywords: Envelhecimento; Restrição vascular; Funcionalidade; Sistema nervoso autônomo; Biomedicina